Morroniside ameliorates sevoflurane anesthesia-induced cognitive dysfunction in aged mice through modulating the TLR4/NF-κB pathway - Jianxing Chen; Bo Peng; Wenqian Lin; Yinjun Mao; Yongsheng Wang (Biomolecules & Biomedicine)
Morroniside (Mor) is a bioactive compound in Cornus officinalis with anti-inflammatory, neuroprotective and antioxidant properties. Prolonged use of the anesthetic sevoflurane (Sev) has been connected to the development postoperative cognitive dysfunction (POCD). This research aims to elucidate the mechanism of action of Mor to improve cognitive impairment. A model of cognitive dysfunction induced by Sev was established in aged mice and tested for behavioral analysis using the water maze experiment. Histopathological changes and neuronal apoptosis in mouse hippocampus were observed by HE staining, Nissl staining, and TUNEL staining. ELISA and qRT-PCR determined the levels of inflammatory factors. Phenotypic transformation of microglia in hippocampal tissue was assessed by immunofluorescence, flow cytometry, and qRT-PCR. The interaction between Mor and TLR4 was analyzed using molecular docking. Western blot identified the levels of apoptosis-related proteins, synapse-related proteins, and TLR4/NF-κB pathway proteins. Inhalation of Sev caused a notable reduction in learning and spatial memory in old mice, which was dose-dependently ameliorated by Mor. Mor inhibited neuroinflammation, modulated the polarization state of hippocampal microglia, promoted their polarization to M2 type, alleviated Sev-induced hippocampal tissue damage and neuronal apoptosis. Notably, Mor can bind well with TLR4 and reduce TLR4-positive expression. Mor blocked Sev-induced TLR4/NF-κB pathway activation in hippocampal tissues, and the TLR4 agonist CRX-527 attenuated the effect of Mor. In conclusion, Mor blocked the TLR4/NF-κB pathway, reducing hippocampal tissue damage and neuroinflammation caused by Sev, which in turn improving cognitive impairment in aged mice.